Comparative Analysis of Islamic Philosophical Foundations and Local Nusantara Wisdom in Building Social Cohesion - Jumai Jumai; Ari Dwi Astono (International Forum of Researchers and Lecturers, 2024)
This study examines the contribution of Islamic philosophy and local wisdom of the archipelago in strengthening social cohesion, with a focus on understanding the values of moderation, harmony, and mutual respect. The background of this research is the increasing social conflict caused by the lack of integrative understanding between Islamic values and local wisdom. The main objective of this study is to assess how these two aspects contribute to creating a more cohesive and harmonious society. This research uses a qualitative approach with hermeneutic methods to analyze Islamic philosophical texts such as taṣawwuf, morals, and kalam, as well as local cultural practices such as customs, mutual cooperation, and other traditions of the people of the archipelago. The results of the study show that Islamic philosophy, with concepts such as salam (peace), akhlak (ethics), and tawhid (unity), plays an important role in building social harmony. Likewise, the local wisdom of the archipelago emphasizes the values of tolerance, cooperation, and togetherness through social practices such as mutual cooperation. The integration of these two elements, i.e. Islamic values and local traditions, has proven to be more effective in strengthening social cohesion when compared to an exclusive approach to one of the sources of value. Therefore, an integrative approach, combining Islamic teachings and local wisdom, is essential to strengthen community bonds and create a more inclusive and harmonious society.